(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The primary linguistic and extralinguistic factors that affect the translation of special economic phrases are revealed in this article. The study’s own linguistic (component and etymological analysis) and pedagogical experience were employed to investigate the intricacies of translating unique economic terminology. It has been demonstrated that the translation language’s cognitive function is largely independent of the language’s grammatical structure. The comprehension of the internal structure of the non-equivalent vocabulary, which articulates the non-differentiation of the species economic notion in the target languages, is crucial to the effectiveness of the translation.